The inclusion of the comunidade santa clara in the information society: proposal work - Farias, Maria Giovanna Guedes (2010)
The Information Science plays a fundamental role in the information society, devising ways to social inclusion through informational inclusion. Accordingly, we present a research proposal for work in development in the Masters Program of Graduate Studies in Information Science at the Universidade Federal da Paraíba, to intervene in the process of informational exclusion experienced by the Comunidade Santa Clara in the city of João Pessoa, Paraíba. This intervention will occur through field research for registration, organization and dissemination of "information sources" consisted of people of the Comunidade. For that we will produce a website where we are going to place for free on the Internet, the “treasure of knowledge” of persons who form the social memory and knowledge of Santa Clara, which will be available for future generations.